Association of Total Ischemic Time With Hospital Length of Stay and Early Graft Function After Living-Donor Kidney Transplantation: A Retrospective Cohort Study - Kusuma, Ardika Satria; Indrawarman, Indrawarman; Ghinorawa, Tanaya (Journal of Applied Nursing and Health, 2026)
Background: Total Ischemic Time (TIT) is a critical determinant of graft survival in deceased-donor transplantation. However, its specific impact on hospital Length of Stay (LOS) and immediate postoperative renal function remains unclear in the context of living-donor transplantation, where ischemic intervals are typically shorter, and graft quality is higher. Methods: This retrospective cohort study, reported according to STROBE guidelines, employed a total sampling technique to analyze 40 living-donor kidney transplant recipients at Dr. Sardjito Hospital. Adult patients with complete operative and laboratory records were included, while pediatric cases and incomplete datasets were excluded. We evaluated the relationship between the independent variable (TIT) and dependent variables (LOS and serum creatinine at Day 1 and Day 7) using Pearson correlation analysis to determine effect sizes and statistical significance. Results: The mean TIT was 90.7 ± 24.0 minutes. Analysis revealed a statistically significant, moderate positive correlation between TIT and LOS (r=0.58, p<0.001). Conversely, the associations between TIT and serum creatinine at Day 1 (r=0.22, p=0.17) and Day 7 (r=0.27, p=0.11) indicated weak positive trends that did not reach statistical significance. Conclusion: While prolonged ischemic time did not immediately compromise graft function in this living-donor cohort, it served as a significant predictor of extended hospitalization. These findings underscore that minimizing ischemic time is crucial not only for biological safety but also for optimizing Kidney Transplantation; Ischemia; Length of Stay; Creatinine; Graft Function.